A novel micro-double cantilever beam (micro-DCB) test in an X-ray microscope to study crack propagation in materials and structures. (September 2018) - Kutukova, Kristina; Niese, Sven; Gelb, Jeff; Dauskardt, Reinhold; Zschech, Ehrenfried
Graphical abstract: In X-ray microscope the miniaturized, piezo-driven mechanical micro double cantilever beam (micro-DCB) test set-up was integrated to visualize crack opening and propagation multi-component material under load. Highlights: Novel micro-DCB technique at X-ray microscope to study in-situ crack evolution. Kinetic studies of crack propagation with a spatial resolution of about 100 nm. 3D visualization of crack opening and propagation. Fracture mechanics investigation of the multi-component materials. Abstract: High-resolution imaging of crack opening and propagation in 3D structures to study the fracture behaviour of materials requires new experimental setups. In this report, we describe a novel technique that provides in-situ 3D visualization of crack evolution with high resolution during mechanical loading of multi-component materials: a micro double cantilever beam (micro-DCB) test in an X-ray microscope. We demonstrate that crack opening and propagation can be visualized (in-situ) in the X-ray microscope with a spatial resolution of about 100 nm. For this experiment, micro-DCB samples were prepared to a thickness that was X-ray transparent in the direction normal to the crack front. During the micro-DCB experiment, the load is applied perpendicular to the optical axis of the X-ray microscope while images are collected with phase contrast imaging. The method is validated for a synthetic polymer, Nafion ® (DuPont) with dispersed platinum particles. The proof-of-concept experiment demonstrates that sub-micron cracks can be visualized non-destructively, and that the in-situ micro-DCB test allows to study crack opening and propagation in materials. The technique offers several benefits over existing methods and is applicable across a range of disciplines, including materials science (e.g. composites), microelectronics, and life sciences (e.g. tissue, bones).